Private Higher Education: Patterns and Trends - Levy, Daniel (International Higher Education, 2008)
Now virtually all the world's regions have private higher education in the large majority of their countries and pre-existing private sectors have grown strikingly. Only with the 1989 fall of communism did private higher education emerge in modern eastern and central Europe and it spread like wild fire in the first half of the 1990s. Private institutions (old and new) continue to be overwhelmingly financed privately (tuition and fees), more hierarchical governance, and mostly in commercial areas. The growth of forprofit sectors are notable. The development of semi-elite private institutions, while majorities are demand-absorbing, are the trend.